Evaluating the Economic Impact of the PedAMINES App in Reducing Medication Errors in Pediatric Emergency Care: Cost-Effectiveness Analysis - Brunner, Loïc; Siebert, Johan N; Ehrler, Frédéric; Manzano, Sergio; Marti, Joachim (Journal of medical Internet research, 2024)
The administration of drugs in pediatric emergency care is a time-consuming process and is associated with a higher occurrence of medication errors compared with adult care. This is attributed to the intricacies of administration, which involve calculating doses based on the child's weight or age. To mitigate the occurrence of adverse drug events (ADEs), the PedAMINES (Pediatric Accurate Medication in Emergency Situations; Geneva University Hospitals) mobile app has been developed. This app offers a step-by-step guide for preparing and administering pediatric drugs during emergency interventions by automating the dose calculation process. Although previous simulation-based randomized controlled trials conducted in emergency care have demonstrated the efficacy of the PedAMINES app in reducing drug administration errors, there is a lack of evidence regarding its economic implications. This study aims to evaluate the cost-effectiveness of implementing the PedAMINES app for 4 emergency drugs: epinephrine, norepinephrine, dopamine, and midazolam. The economic evaluation was conducted by combining hospital data from 2019, previous trial outcomes, information extracted from existing literature, and PedAMINES maintenance costs. The cost per avoided medication error was calculated, along with the number of administrations needed to achieve a positive return on investment. Subsequently, Monte Carlo simulations were used to identify the key parameters contributing to result uncertainty. The study revealed the number of preventable errors per administration for the 4 examined drugs: 0.513 for epinephrine, 0.484 for norepinephrine, 0.500 for dopamine, and 0.671 for midazolam. The cost-effectiveness ratios per ADE prevented were computed as follows: US $4808 for epinephrine, US $9705 for norepinephrine, US $6957 for dopamine, and US $2074 for midazolam. Accounting for the economic impact of ADEs, the analysis estimated that 16 administrations of epinephrine, 17 of norepinephrine and dopamine, and 13 of midazolam would be required to attain a positive return on investment. This corresponds to roughly one-third of the annual administrations at a major university hospital in Switzerland. The primary factors influencing the uncertainty in the estimated cost per ADE include the cost of maintenance of the app, the likelihood of an ADE resulting from an administration error, and the frequency of underdosing in the trial's control group. A dedicated mobile app presents an economically viable solution to alleviate the health and economic burden of drug administration errors in in-hospital pediatric emergency care. The widespread adoption of this app is advocated to pool costs and extend the benefits on a national scale in Switzerland.